Clinical characteristics and outcomes of patients with ventricular arrhythmias after continuous‐flow left ventricular assist device implant. Issue 8 (21st March 2022) - Gulletta, Simone; Scandroglio, Anna Mara; Pannone, Luigi; Falasconi, Giulio; Melisurgo, Giulio; Ajello, Silvia; D'Angelo, Giuseppe; Gigli, Lorenzo; Lipartiti, Felicia; Agricola, Eustachio; Lapenna, Elisabetta; Castiglioni, Alessandro; et al.
Abstract: Background: Ventricular arrhythmias (VAs) are observed in 25%–50% of continuous‐flow left ventricular assist device (CF‐LVAD) recipients, but their role on mortality is debated. Methods: Sixty‐nine consecutive patients with a CF‐LVAD were retrospectively analyzed. Study endpoints were death and occurrence of first episode of VAs post CF‐LVAD implantation. Early VAs were defined as VAs in the first month after CF‐LVAD implantation. Results: During a median follow‐up of 29.0 months, 19 patients (27.5%) died and 18 patients (26.1%) experienced VAs. Three patients experienced early VAs, and one of them died. Patients with cardiac resynchronization therapy (CRT‐D) showed a trend toward more VAs ( p  = 0.076), compared to patients without CRT‐D; no significant difference in mortality was found between patients with and without CRT‐D ( p  = 0.63). Patients with biventricular (BiV) pacing ≥98% experienced more frequently VAs ( p  = 0.046), with no difference in mortality ( p  = 0.56), compared to patients experiencing BiV pacing <98%. There was no difference in mortality among patients with or without VAs after CF‐LVAD [5 patients (27.8%) vs. 14 patients (27.5%), p  = 0.18)], and patients with or without previous history of VAs ( p  = 0.95). Also, there was no difference in mortality among patients with a different timing of implant of implantable cardioverter‐defibrillator (ICD), before and after CF‐LVAD ( p  = 0.11). Conclusions: VAs in CF‐LVAD are a common clinical problem, but they do not impact mortality. Timing of ICD implantation does not have a significant impact on patients' survival. Patients with BiV pacing ≥98% experienced more frequently VAs. Abstract : We reported a retrospective study in which we analyzed 69 consecutive CF‐LVAD‐carrier patients. In these patients, ventricular arrhythmias are a common clinical problem, but they do not impact mortality. Timing of ICD implantation does not have a significant impact on patients' survival. Patients with biventricular pacing for ≥98% of the time experienced more frequently VAs.